Complexities of financial globalisation analytical and policy issues in emerging and developing economies - Cavoli, Tony; Gopalan, Sasidaran; Rajan, Ramkishen S. (Routledge, 2020)
"Since the 1990s, several emerging market and developing economies (EMDEs) have, to varying degrees, embraced the process of financial globalisation, broadly defined as a set of policies that involve allowing for greater openness to cross-border capital flows as well as greater market access to foreign financial institutions. This book provides a systematic empirical analysis on the complex interactions between financial sector development, macroeconomic and financial stability in EMDEs in general and those in the Asian region in particular. The book consists of three sections pertaining to monetary and exchange rate policies under financial globalisation; financial inclusion and macroeconomic policies in the context of financial liberalisation; and finally, the dynamics of foreign direct investment flows and their real impacts in EMDEs. Each of the chapters analyse important economic policy issues of contemporary relevance and is informed by data and rigorous empirical analysis. The book will be appealing to anyone interested in exploring the implications of a key set of issues emanating from financial globalisation on EMDEs in a rigorous but readable manner"--
Description based on online resource; title from digital title page (viewed on June 04, 2020)
Keywords: International finance; Macroeconomics; Investments, Foreign / Developing countries